Analisis Implementasi Sistem Manajemen Biorisiko Pada Laboratorium Pendidikan Kesehatan Di Universitas Bali Internasional - Made Adhyatma Prawira Natha Kusuma; I Gusti Agung Ayu Satwikha Dewi; I Gusti Agung Haryawan (Indonesian Journal of Health Community, 2025)
All laboratory activities significantly impact health, especially wet laboratories. This is due to the potential hazards and high risk of workplace accidents. The purpose of this study was to determine the implementation of the biorisk management system in the laboratory of Bali International University. The approach used was quantitative, conducted by completing the SNI 8340:2016 checklist through laboratory interviews and direct observation in the laboratory. The study uses biological materials from December 2023 to December 2024. The unit of analysis for this study were four laboratories. After data processing for all laboratories had been calculated, a gap analysis was determined. The results show that four laboratories studied have not yet established a biorisk management system. There has been no achievement related to the general requirements and policy aspects, the average achievement in the planning aspect needs to be improved, namely 26%. The average achievement in the implementation and operational aspects is good, namely 61%, and the average achievement in the inspection and corrective action aspects is good, namely 61%. Management reviews have not been conducted at all laboratories. The recommendation that can be given is to develop policies related to risk management and implement them comprehensively.